Carotid body enlargement in hypertension and other comorbidities evaluated by ultrasonography. Issue 7 (July 2019) - Tan, Jie; Xiong, Bo; Zhu, Yefeng; Yao, Yuanqing; Qian, Jun; Rong, Shunkang; Yang, Gang; Zhu, Que; Jiang, Yonghong; Zhou, Qi; Liu, Dichuan; Deng, Changming; et al.
Abstract : Background: Carotid body hyperactivity is important for sympathetic-related diseases and carotid body volume may partly reflect carotid bodies' activity. Our objective was to identify the association between carotid body volume and hypertension or other sympathetic-related diseases. Methods: Consecutive individuals, undergoing carotid ultrasonography, who were eligible for the inclusion criteria were included. The bilateral carotid bodies were detected and volumetric parameters were measured by carotid ultrasonography in clinical. Clinical data of included participants were collected and analysed. Results: A total of 1226 consecutive individuals underwent carotid ultrasonography. Carotid bodies were detected as solid, pebble-shaped, hypoechoic structures and the overall carotid body detection rate was 78.7% (965/1226). Univariate and multivariate regression analyses indicated that hypertension, chronic heart failure (CHF), chronic lung disease, smoking and high BMI were positively associated with carotid body enlargement. Compared with controls (2.63 μl), carotid body volume was significantly elevated in simple hypertensive (3.11 μl, P  < 0.001), simple CHF (3.27 μl, P  = 0.004) and simple smoking (3.47 μl, P  < 0.001) groups. Moreover, the individuals with three comorbidities (4.05 μl) had significantly larger carotid bodies than those with one (3.23 μl, P  < 0.001) or two comorbidities (3.46 μl, P  = 0.017), suggesting that there existed a cumulative effect of comorbidities on carotid body volume. Conclusion: Carotid body enlargement is strongly associated with hypertension and other sympathetic-related diseases or risk factors, and carotid body volume evaluated by carotid ultrasonography may be further explored as a promising screening and evaluation predictor for carotid body modulation therapy in patients with hypertension and other sympathetic-related diseases.